The crisis of value, 'right-wing populism' and the prospects for human emancipation. Issue 3 (2nd October 2021) - Azeri, Siyaves
Abstract : Today's rise of far-right-wing politics and dictatorial regimes is an expression of the fundamental tensions of the social relations resulting from capitalism's own development – the contradiction between the production of 'real wealth' that 'comes to depend less on labour time' and the form of labour employed, which yields 'the crisis of value'. This crisis, which also amounts to the intensification of 'class struggle' – with class being understood as 'a politically mediated fluid being that is logically preceded by its conceptuality' – also denotes the possibilities for the constitution of revolutionary-emancipatory consciousness as the subject of building a communist society. Right-wing populism is the political means of the continuous constitution of the social domination of capital that is incarnated in the form of the state: it is the political form the state assumes in the face of the perpetual crisis of capital and the consequent state of emergency.